Ideal Water Tourism Concept as an Effort to Realize a Blue Economy for Wonosari Village Communities - Sabri, Muhammad; Halim Dwi Putra; Doris Sukma (Politeknik Negeri Bengkalis, 2023)
This study aims to analyze the concept of ideal water tourism as an effort to create a blue economy for the community. This research uses a qualitative approach with the method of literature study and content analysis. The data was collected through searching scientific literature, journals, books, research reports, and other related sources of information such as community surveys in the city of Bengkalis. The data is then analyzed systematically to identify the ideal water tourism concept that supports the blue economy for the community at Wonosari Village, Bengkalis. The results of the study show that the concept of ideal water tourism in the blue economy context involves several important aspects. First, sustainable environmental management, including reducing waste, conserving water resources, and protecting aquatic ecosystems, is a key prerequisite. Second, the active participation of local communities in the development and management of water tourism is an important key to ensuring a positive impact on the local economy and people's welfare. In addition, the concept of ideal water tourism that supports the blue economy also includes the integration of social and cultural principles. Empowerment of local communities, community-based sustainable economic development, and preservation of maritime cultural heritage are important components in achieving blue economy goals through water tourism. The findings of this research can be used by governments, decision makers and related stakeholders in planning and developing sustainable water tourism destinations and contributing to sustainable economic growth. Keywords: Blue Economy, Water Tourism, Wonosari Village